1988
DOI: 10.1111/j.1440-1754.1988.tb01329.x
|View full text |Cite
|
Sign up to set email alerts
|

Haematolytic disease due to ABO incompatibility: Incidence and value of screening in an Asian population

Abstract: The population in Singapore is predominantly Asian, with Chinese forming the major ethnic group. The incidence of haemolytic disease of the newborn (HDN) due to Rh incompatibility is very low. The true incidence of HDN due to ABO incompatibility is unknown. Early discharge is practised in Singapore making it important to predict severe HDN due to ABO incompatibility as this would constitute the main cause of haemolysis next to G6PD deficiency. One thousand, six hundred and eight baby‐maternal pairs were typed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
0
10
1
1
Order By: Relevance
“…In an earlier published study the sensitivity and specificity were lower at 53 and 73%, respectively. 8 The low positive predictive value of the newborn DAT for clinically significant ABO HDN has been confirmed previously 9,10 and a number of studies have concluded that routine testing is not necessary. 7,[11][12][13][14] Conversely, evidence exists to support that a positive DAT is associated with an increased incidence of jaundice and more severe ABO HDN.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In an earlier published study the sensitivity and specificity were lower at 53 and 73%, respectively. 8 The low positive predictive value of the newborn DAT for clinically significant ABO HDN has been confirmed previously 9,10 and a number of studies have concluded that routine testing is not necessary. 7,[11][12][13][14] Conversely, evidence exists to support that a positive DAT is associated with an increased incidence of jaundice and more severe ABO HDN.…”
Section: Discussionmentioning
confidence: 84%
“…The low positive predictive value of the newborn DAT for clinically significant ABO HDN has been confirmed previously 9,10 and a number of studies have concluded that routine testing is not necessary 7,11–14 …”
Section: Discussionmentioning
confidence: 84%
“…3 Various screening tests for predicting severity have been studied. 2,4,6,11,12 However, some studies have found that routine screening tests for predicting ABO haemolytic disease are not helpful 13,14 and thus are not cost-effective.…”
Section: Discussionmentioning
confidence: 98%
“…Kiruba RHP et al in his study found out that it was 3.7%. 7 Present study showed that the cord bilirubin >1.8mg/dl and hemoglobin <15.1gm/dl were more prone for pathological hyperbilirubinemia. This was similar to the previous study by Rataj et al in which cord bilirubin of >2.5 were prone for pathological jaundice.…”
Section: Discussionmentioning
confidence: 46%